CATUSPATHA KONSEP, TRANSFORMASI, DAN PERUBAHAN - Putra, I Gusti Made (Jurnal Natah; Vol. 3, No. 2 Agustus 2005, 2012)
Catuspatha has a meaning not just a simple word “crossroad” but it means a crossroad which has a sacred value and a specific meaning and known as pempatan agung. At kingdom era, the catuspatha is as center of kingdom and this means that it is a center of country. While, since colonialism of the Netherlands in Bali, there are an idea to put aesthetic elements as focal point or city landmark at core of the catuspatha. Furthermore, this idea is obviously pursued by republic government on independent era. The aim of the research is to explore evidently concept of the catuspatha, the transform of the concept and changes of the catuspatha as a kingdom center from the kingdom era till the republic era and its impact. This research have been conducted through surveying on nine catuspatha as heritage of the kingdom era in Bali, collecting literatures, and interviewing the priest of siwa, budha, bujangga and other main actors as well. The research shows that there are any critical changes of the catuspatha. Firstly, it is the change of idea or perspective of the catuspatha. The center of the catuspatha as an empty space has changed to be the aesthetic element of the city and even it has been operated as traffic sign and orientation. Secondly, regarding to political context, it has influence to the tradition values of the catuspatha. The symbolism of the kingdom authority which is expressed obviously on arrangement of palace with its facilities is changed as town hall and other offices. Thirdly, with regards to transportation technology, on the catuspatha, it is located traffic signs to manage and control the traffic flow.
Keywords: catuspatha, crossroads, pempatan agung